2020
DOI: 10.3390/su12030853
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evidence in Ecuador between Economic Growth and Environmental Deterioration

Abstract: Currently, obtaining evidence of the correlation between economic growth and environmental deterioration is of great relevance. Due to an increase in economic activity, an increase in CO2 emissions and its possible effects on the current climate change is very worrying. The studies that analyze this correlation serve as a basis for the awareness of countries and the establishment of policies worldwide to curb such deterioration. The objective of this research is achieved through a panel data model and spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 78 publications
0
6
0
1
Order By: Relevance
“…Therefore, there is a need for closer international cooperation in this area. Many studies also confirmed the existence of relationships consistent with the environmental Kuznets curve-i.e., the dependence of environmental impact on the level of economic development of the country [60][61][62][63][64]. However, in developing countries, there are differences in the relationship between economic growth in energy use and renewable energy.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, there is a need for closer international cooperation in this area. Many studies also confirmed the existence of relationships consistent with the environmental Kuznets curve-i.e., the dependence of environmental impact on the level of economic development of the country [60][61][62][63][64]. However, in developing countries, there are differences in the relationship between economic growth in energy use and renewable energy.…”
Section: Resultsmentioning
confidence: 99%
“…Some significant variables and cardinal sustainable development indicators identified as relevant to this study [ 13 , 18 , 22 , 23 , 30 , 31 ] include the following: economic-dynamics : employment, GDP; enviro-dynamics : land use, water use, GHG (CO2) emissions, heavy metal emission; socio-dynamics : displacement, infrastructure, public services, and farming /fishing.…”
Section: Methodology—a Model Structurementioning
confidence: 99%
“…The changes could include technological innovations. Researchers [ 23 ] observed from their study that economic growth often results in environmental deterioration in the short run. Successful mitigation of mismatch (“economic development and environmental sustainability”) requires identifying the prohibiting factors to sustainable development, using data analyses and other approaches [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of investigations in the last two decades have focused their analyses on observing what the determinants of environmental pollution are (Ahmad et al, 2017; Audi & Ali, 2018; Massa‐Sánchez et al, 2020; among others). Research shows that aggregate economic activity, in addition to population growth (Katircioglu et al, 2020), is the main driver of environmental deterioration.…”
Section: Introductionmentioning
confidence: 99%